Use of Learning Media to Increase Student Motivation in Junior High School - Suyahman, Suyahman; Pattiruhu, Claudia Monique; Zuhriyah, Aminatuz; Rintaningrum, Ratna; Manyullei, Syamsuar (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The development of the times greatly affects life, one of which is in the field of education, many innovations related to education, one example is the use of learning media in the teaching and learning process and motivation. Lots of learning innovations that produce technology that makes it easier for an educator to provide learning material so that students get motivation to learn. Learning media is very useful in every lesson at the Junior High School level. This study aims to determine the application of the use of any media that can influence and encourage students' learning motivation at the Junior High School level. This type of research is descriptive qualitative research. Data obtained through observation, interviews and documentation. The results showed that the use of learning media on students' learning motivation greatly supported motivation in learning activities. Students are very motivated when the learning uses projector media and speakers. In addition, the use of learning media at the junior high school level has an important role in the interest and motivation of students to learn, including feelings of pleasure and interest in the material increases. The implication of this research is that educators in delivering learning materials in the classroom must be good at choosing and using the right media, educators must also have creative and innovative ideas so that the learning atmosphere of students is more enthusiastic and motivated. The limitation of this study is that researchers only observed one school, therefore researchers hope that future researchers can observe more schools and better ways.